Conditions of social vulnerability, work and low income, evidence for Spain in comparative perspective - Teresa Munzi; Timothy Smeeding (Luxembourg Income Study (LIS), 2006)
Social vulnerability due to insufficient income and earnings may come from many sources, both demographic and economic, in a globalizing world. This paper examines the problems of population aging, low wages, growing inequality, low work hours and insufficient social spending in Spain .Vulnerable groups such as children and the aged are considered. The paper will look at the United States, Canada, and Europe using the LIS (Luxembourg Income Study) database, and especially with a focus on Spain. For the first time we compare the similarities and differences between a set of Mediterranean LIS nations: Spain, Italy and Greece, compared to their European and OECD counterparts. We will assess the net effects of existing policies on poverty and inequality, and particularly the United Kingdom's recent program to reduce child poverty. While best practices may be identified, each nation must create its own set of mutually supportive policies which provide protection against global economic forces while at the same time encouraging self effort and efficient behavior, especially in the labor market. In the end, policy can make a difference in outcomes, as shown by the recent British success in fighting child poverty.
Keywords: 330